Evaluasi Pelaksanaan Clinical Pathway: Scoping Review - Dwi Natalia Rustanti; Wida Kuswida Bhakti; Suriadi; Ramadhaniati (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Improving the quality of healthcare and patient safety is a top global priority. Clinical Pathways (CP) are implemented as evidence-based management tools to reduce clinical practice variations and enhance efficiency. However, implementation success varies significantly across organizations, necessitating systematic evaluation to identify adherence barriers and the effectiveness of these instruments on hospital quality indicators. Objective: This study aims to map the literature regarding the evaluation of Clinical Pathway implementation in hospitals, including the instruments used and the dimensions focused on during the evaluation process. Methods: This scoping review follows the Arksey and O’Malley framework and JBI guidelines. Literature searches were conducted across PubMed, ScienceDirect, and Scopus databases for articles published between 2021 and 2025. The study selection process utilized the PRISMA-ScR flow diagram. Results: From 465 identified articles, 5 studies were selected for synthesis. The evaluation results demonstrate that CP implementation consistently reduces the risk of complications, such as decreasing C. difficile recurrence rates from 29.2% to 15.1% and reducing the incidence of delirium in elderly hip fracture patients. CPs were also effective in shortening the Length of Stay (LOS) and improving diagnostic accuracy through digital technology integration. The main challenges identified included low adherence (52%) in heterogeneous medical conditions and the perception of increased administrative workload for healthcare professionals. Conclusion: The evaluation of Clinical Pathway implementation proves its significant potential in transforming healthcare services to be safer and more efficient. CP success depends not only on the clinical design of the flow but also on implementation strategies, technological support such as Electronic Health Record (EHR) integration, and the acceptance of frontline healthcare workers.